Economic loss from liver condemnation due to Fasciolosis in slaughtered ruminants in Maiduguri abattoir, Borno State, Nigeria - Liba, James Wabba; Atsanda, Naphtali Nayamanda; Francis, Markus Isa (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: The study was conducted to evaluate economic loss from liver condemnation due to Fasciolosis in slaughtered ruminants in Maiduguri abattoir, Borno State, Nigeria. Materials and methods: Three hundred (300) livers each of cattle, sheep and goats slaughtered were randomly selected and examined for the presence of Fasciola flukes. The infected livers were weighed and economic value in Nigerian Naira (?) and US Dollar (US) were assessed. Results: An overall economic loss of ?602,400.00 (1,882.50 US) per annum was incurred during the period under study from a total of 753 kg of liver condemned. Total of 428 kg and 325 kg of liver were condemned during dry and rainy seasons respectively, resulting in higher economic loss of (?342,400.00; 1,070 US) in dry season and (?260,000.00; 812.50 US) during rainy season. More liver were condemned in the adult cattle (372 kg) than in adult sheep (117 kg) and goats (108 kg) during the period of this study. Conclusion: Ruminant fasciolosis is endemic in Maiduguri, and high economic loss for the farmers and butchers are reported in this study. Strengthening and developing better control methods of fasciolosis in ruminants in Borno State is suggested. http://doi.org/10.5455/javar.2017.d192